Ixodes schulzei Aragão & Fonseca, 1951 in Argentina - Lamattina, Daniela; Venzal, José Manuel; Guglielmone, Alberto Alejandro; Nava, Santiago (2017)
Two females of Ixodes schulzei Aragão & Fonseca, 1951 were collected from Nectomys squamipes (Rodentia: Cricetidae: Sigmodontinae) at Iguazú National Park, Misiones Province, Argentina. This is the first record of this tick species in Argentina. All previous records of I. schulzei came from Brazil (some of them close to the border with Argentina) where larvae, nymphs and females of I. schulzei have been found parasitizing Sigmodontinae hosts. The current record of I. schulzei has been expected and its range may include Paraguay.